45 years' experience with early childhood anatomical technique of feminising genitoplasty for 46 XX Congenital Adrenal Hyperplasia –observations of vaginal introital anatomy and its relationship to the perineal body. Issue 5 (October 2022) - Hennayake, Supul; Barnes, Abigail; Mariotto, Arianna; Goyal, Anju; Ajao, Akinlabi; Cserni, Tamas; Busby, Gail; Patel, Leena; Skae, Mars; Nicholson, Jacqueline; Bianchi, Adrian
Summary: In Manchester, feminising genitoplasty is offered to children with 46XX Congenital Adrenal Hyperplasia (CAH) when there is a single perineal opening and/or enlarged clitoris. Our aims are to describe the anatomical reconstructive technique and present long-term outcomes. Our hypothesis is that 'the common channel (CC) length and distance to the vagina from perineal skin is mostly due to virilisation and hypertrophy of perineal tissue over the almost normally positioned vaginal introitus (V–I) in relation to the perineal body (PB)'. Method and results: This is a retrospective notes review of all consecutive 46XX CAH operations from 1976 to December 2021. 99 patients, who had feminising genitoplasty and being followed-up, were included. 15 patients who were lost to follow up were excluded. Median age at surgery was 15 months. In 91, midline division of the labia majora, spongiosum, bulbo-spongiosus muscle (BSM) and CC down to PB was performed. This was sufficient to expose the V–I at the same level or within 5 mm depth of PB in 88. In 78 V–I was adequate taking 10/12fr dilator (Type 1). In 10, CC resembled a male urethra and V–I was narrow (Type 2), requiring widening by 5–10 mm incision at 6 o'clock position. Dartos of labia majora was attached to BSM to reduce the distance to V–I from perineal skin and the gap was lined with inner foreskin to create a vestibule. Out of 70 who were post-pubertal, 75% (53/70) had adequate calibre vaginal openings. 5 had introitoplasty and 2 had dilatation under anaesthesia. 10 needed self dilators only. 29 patients, of one of the three surgeons, had measurements of clitoris, CC, urethra and vagina. A hymen was found in 86% (25/29). There was significant strong, inverse correlation between the CC length and the urethral length (r = −0.708, p < 0.001, n = 27) but not between CC and vaginal lengths. After adjusting for age, the urethral length of Type 2 patients was 3.825 mm shorter than those of Type 1 (p = 0.017). Conclusion: Our data show that 'high' confluence is mostly due to virilisation of genitalia; and the anatomical technique of reversing the fusion of the urethral folds, spongiosum and bulbo-spongiosus muscle could be performed with all degrees of virilisation with success in early childhood with no need of local flaps or mobilisation of the urethro–vaginal complex. About 10% require surgery to treat narrowing of vaginal opening post puberty. Summary table Summary table Total patients: 99 No. Median age at op Anatomy (n=99) Type of common channel (n=99) Separate urethral and vaginal openings 8   Typical 'common channel'- Type 1 78   Male urethral type- Type 2 13   Median lengths at surgery of a subset of 29 patients (n=27) Clitoris 25 mm     Common channel 25 mm     Urethra 15 mm     Vagina 40 mm     Extent of Primary surgery (n=99) Feminising genitoplasty 91 15 months     Clitoral reduction only 8 36.5 months Post pubertal outcome (n=70) Vaginal introital stenosis-24% (17/70) Mild stenosis needing self dilatation only 10   Severe stenosis needing surgery Introitoplasty 5 17 years Dilatation in theatre 2 Clitoral outcome Enlarged clitoris requiring re-reduction 2 16 years